India : 2005 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2006)
India's 2005 Article IV Consultation reports that the government's medium-term fiscal strategy is broadly appropriate, and faster implementation is crucial for its economy. India's growth spurt provides a golden opportunity to fast-forward the government's structural reform agenda. The government is rightly focused on improving the infrastructure, opening and liberalizing further the Indian economy, and alleviating poverty. Steps to improve the business climate and regulatory environment, and reform of restrictive labor laws could have large payoffs in terms of foreign investment and job creation.